The GCF is x.
The GCF is 3.
The GCF is 1.
3(3x + 5)
3x. 15x - 9x = 6x 9x - 6x = 3x 6x - 3x = 3x 3x - 3x = 0
9 This expression can be simplified to: 9x
Honey, that's not a linear equation, so there's no slope-intercept form to be found here. You've got a monomial mess on your hands with 9xy. If you want to simplify it, just leave it as 9xy. No need to force it into a form it doesn't belong in.
The GCF of 6x and 9x is 3x
The GCF is 5x
the LCM of (a) and (b) is (ab) divided by (gcf of a and b) In this case, (a)=9 (45) = (9x)/(1) 45 = 9x 5= x ◄
24
9x+6 = 6x+15 9x-6x = 15-6 3x = 9 x = 3